Reversible synthesis of colanic acid and O-antigen polysaccharides in Salmonella Typhimurium enhances induction of cross-immune responses and provides protection against heterologous Salmonella challenge. Issue 21 (15th May 2017) - Li, Pei; Liu, Qing; Huang, Chun; Zhao, Xinxin; Roland, Kenneth L.; Kong, Qingke
Highlights: The products of cps G and rfb K in Salmonella are isozymes for mannose synthesis. The Δ cpsG Δ rfbK mutant produces full length O-antigen in the presence of mannose. Salmonella with two mutations enhance induction of IgG cross-reactive with OMPs. Abstract: Colanic Acid (CA) and lipopolysaccharide (LPS) are two major mannose-containing extracellular polysaccharides of Salmonella . Their presence on the bacterial surface can mask conserved protective outer membrane proteins (OMPs) from the host immune system. The mannose moiety in these molecules is derived from GDP-mannose, which is synthesized in several steps. The first two steps require the action of phosphomannose isomerase, encoded by pmi ( manA ), followed by phosphomannomutase, encoded by manB . There are two copies of manB present in the Salmonella chromosome, one located in the cps gene cluster ( cpsG ) responsible for CA synthesis, and the other in the rfb gene cluster ( rfbK ) involved in LPS O-antigen synthesis. In this study, it was demonstrated that the products of cpsG and rfbK are isozymes. To evaluate the impact of these genes on O-antigen synthesis, virulence and immunogenicity, single mutations (Δ pmi, Δ rfbK or Δ cpsG ) and a double mutation (Δ rfbK Δ cpsG ) were introduced into both wild-type Salmonella enterica and an attenuated Δ cya Δ crp vaccine strain. The Δ pmi, Δ rfbK and Δ cpsG Δ rfbK mutants were defective in LPS synthesis and attenuated for virulence. In orally inoculated mice, strain S122 (Δ crp Δ cya Δ cpsG Δ rfbK ) and its parent S738 (Δ crp Δ cya ) were both avirulent and colonized internal tissues. Strain S122 elicited higher levels of anti- S . Typhimurium OMP serum IgG than its parent strain. Mice immunized with S122 were completely protected against challenge with wild-type virulent S. Typhimurium and partially protected against challenge with either wild-type virulent S. Choleraesuis or S. Enteritidis. These data indicate that deletions in rfbK and cpsG are useful mutations for inclusion in future attenuated Salmonella vaccine strains to induce cross-protective immunity.